Impact of Technology Use in Knowledge Management on Innovative Output in Organizations: A Comprehensive Analysis (International Journal of Food and Nutritional Sciences, 2023)
This research paper investigates the impact of technology use in knowledge management (KM) on theinnovative output of organizations